A hora dos direitos epistêmicos e do direito ao grito: Clarice Lispector uma intelectual da(s) lei(s) - BÁRBARA ARTUZO SIMABUCO (2023)
The present dissertation, entitled THE TIME OF EPISTEMIC RIGHTS AND THE RIGHT TO SCREAM: Clarice Lispector, an intellectual of the law(s), has as main objective to compare, under the prism of difference, the concept of epistemic rights (MIGNOLO, 2008) with the right to scream present in The time of the star (1977). The specific objectives consist of determining myself in the practice of development elaborated and worked on by the intellectual since she was undergraduated in Law, focusing on the concept of Development, in particular through the essay “Observations on the Right to Punish” (1941). The next objective is point out about the concept of exteriority in the narrative construction of The time of the star. I aim to articulate a bios critique of the book, focusing on memory, the archive and the concept of exteriority. I also aim to discuss the epistemic disobedience proposed by the intellectual in the construction of The time of the star, passing through the right to scream, focusing on the concept of epistemic disobedience. Key words: Frontier biographic criticism; Epistemic rights; Right to scream; Clarice Lispector; The time of the star.